Uso de fibras de abacá para la elaboración de un mortero con capacidad de deformación mejorada para enlucidos - Baño García, Vanessa Nataly (2024)
This research explored the use of abaca fibers in mortar production. The fibers, treated with sodium hydroxide (NaOH) to enhance their adhesion, were cut to 1.2 cm. They were added in proportions of 0.3%, 0.5%, and 0.75% during Phase 1. It was observed that the setting time with the inclusion of NaOH-treated fibers is faster compared to a control mortar without fibers. Compression tests found that a 1:5 ratio (cement: fine aggregate) does not meet the necessary strength for this type of mortar when different fiber percentages are included. Therefore, in Phase 2, the amount of fine aggregate was reduced, and dosages of 1:4.4 with 0.3% fiber and 1:3.4 with 0.5% fiber were used. The results of the bending and compression tests conducted in Phase 1 led us to discard the dosage of 0.75% fiber because this addition percentage reduces its mechanical properties compared to the fiber-reinforced dosages at 0.3% and 0.5%. It's worth mentioning that the fiber formed agglomerations within the mixture that hindered workability. In addition to preparing cube and prism specimens for compression and flexural tests, prismatic specimens called FRCM (Fiber-Reinforced Composite Material) were also fabricated. These were tested for bending and tensile strength to simulate the behavior of the mortar under these loads. The results were promising, but further research is needed. This graduation project has demonstrated abaca fibers' potential in improving mortars' strength and deformability. However, additional investigation is required to optimize fiber dosages and fully understand the behavior of abaca fiber-reinforced mortar under actual construction conditions.